1973
DOI: 10.1073/pnas.70.5.1593
|View full text |Cite
|
Sign up to set email alerts
|

Conformations of Diphosphopyridine Coenzymes upon Binding to Dehydrogenases

Abstract: The binding of oxidized as well as reduced coenzyme to some dehydrogenases has been studied under different concentration ratios and temperatures by nuclear magnetic resonance spectroscopy. A significant difference in the spectral behavior between DPN+ and DPNH upon binding is interpreted in terms of fast and slow on-off rates relative to the nuclear magnetic resonance time scale in the binding of these two coenzymes. Significant downfield shifts of DPN+ were observed upon binding, comparable in magnitude to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1973
1973
1997
1997

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…A recent report from our laboratory has described the configuration that NAD+ assumes upon binding to any of a number of dehydrogenases (21). In nearly all cases, evidence was obtained consistent with the view that destacking of NAD+ accompanies binding at the coenzyme site.…”
mentioning
confidence: 58%
“…A recent report from our laboratory has described the configuration that NAD+ assumes upon binding to any of a number of dehydrogenases (21). In nearly all cases, evidence was obtained consistent with the view that destacking of NAD+ accompanies binding at the coenzyme site.…”
mentioning
confidence: 58%
“…These results broadly support the view, originally put forward by Velick (1961), that the mode of binding of NAD+ to glyceraldehyde 3-phosphate dehydrogenase differs considerably from its mode of binding to lactate and malate dehydrogenases (see, e.g., the recent n.m.r. studies by Lee et al, 1973).…”
Section: Discussionmentioning
confidence: 98%
“…A number of studies have shown that this coenzyme mainly assumes a stacked conformation in solution. In contrast, X-ray diffraction analysis has indicated an extended NAD conformation when bound in biochemical systems. ,, Knowledge of the factors influencing the folding process would be desirable and could lead to an increased understanding of the role of this cofactor in enzymatic redox reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques have been used to identify the conformations assumed by NAD in different environments such as aqueous solution, binding to enzymes or metal ions, ,, crystallization, , or adsorption on metal surface. Because a charged metal surface may serve to mimic a biological interface and provide informatioin about the electrochemistry of the bound NAD, there is considerable interest in studies of such models. However, most of such measurements reported previously were performed under ex-situ conditions, and the proposed conformation models were usually based upon indirect evidence.…”
Section: Introductionmentioning
confidence: 99%